Solovey and Cravens: Cold War Social Science - Bortolini, Matteo (Serendipities. Journal for the Sociology and History of the Social Sciences, 2016)
Book Review of: Mark Solovey and Hamilton Cravens (eds.), Cold War Social Science: Knowledge Production, Liberal Democracy, and Human Nature New York: Palgrave Macmillan 2014 First paperback ed., xvii + 270 pp. ISBN 978-1-137-38835-3 Price: € 31